(Invited) Ion Implantation into GaN and Implanted GaN Power Transistors. (21st September 2015) - Nomoto, Kazuki; Takahashi, Kengo; Takuya, Oikawa; Ogawa, Hiroki; Nishimura, Tomoaki; Mishima, Tomoyoshi; Xing, Huili Grace; Nakamura, Tohru
Abstract : We report great possibilities of ion implantation technology for applying to high-power GaN electron devices. We demonstrated high-performance normally-off self-aligned metal gate GaN MISFETs with Si ion implantation to reduce the contact resistances for ohmic contacts and N ion implantation for the device isolation. We formed p-type GaN in n-type GaN using Mg ion implantation and observed p-n junction diode behavior on forward I-V characteristics and EL measurements.